Educational Attitudes Deduced from the Scientific Methodology of Aisha, may Allah be Pleased with her - Alzahrani, Layla Ahmad Alhesni (Journal of Educational and Psychological Sciences, 2022)
This research aims to monitor the factors constituting the scientific personality of Aisha, may Allah be pleased with her, to clarify her methodology in education, and to identify the educational attitudes deduced from her scientific life. The research adapted the deductive approach and resulted in that Mother of Believers, Aisha, May Allah be pleased with her, inherited a realistic methodology in distributing the roles of the educational process pillars. She originated a set of scientific steps in cognitive achievement. In Addition to the close relationship between her educational attitudes deduced from her scientific life and the faith, the first pillar in building the learner’s scientific personality.